Perlindungan Hukum Bagi Perempuan dan Anak di Negara-Negara Muslim Modern Perspektif Mubadalah - Mu'in, Fathul; Fathul; Gandhi Liyorba Indra; Relit Nur Edi; Rudi Santoso; Diah Mukminatul Hasimi (Institut Agama Islam Negeri Metro, 2025)
Abstract: The issue of legal protection for women and children remains a crucial concern in many Muslim countries, particularly regarding gender inequality, domestic violence, and limited access to justice. Although Islam upholds the principles of justice and respect for human dignity, its implementation is often influenced by patriarchal culture and legal systems that have yet to fully protect vulnerable groups. Based on this background, this study aims to analyze the forms and implementation of legal protection for women and children in Saudi Arabia, Egypt, and Indonesia through the mubadalah (reciprocity) perspective. This research is a qualitative library study using normative and comparative approaches, drawing on Islamic legal sources, national legislation, and relevant academic literature. The results indicate that Saudi Arabia remains oriented toward classical fiqh but is beginning to transform through legal reform; Egypt has progressively codified family law; while Indonesia integrates Islamic justice principles with national law through comprehensive regulations protecting women and children. From the mubadalah perspective, all three countries demonstrate efforts toward more equal and just legal relations, affirming that true legal protection must be grounded in reciprocity, humanity, and gender justice. Keywords: Protection, Women and Children, Muslim Countries, Mubadalah